Are Bone Turnover Markers Related with Fracture Risk in Initial Diagnose Postmenopausal Osteoporosis? A Cross-Sectional Clinical Study - Şeniz Akçay Yalbuzdağ; Banu Sarıfakıoğlu; İlker Şengül; Nuri Çetin (Türk Osteoporoz Dergisi, 2015)
Objective: In this study, we investigated the relationships between 10 year fracture risk calculated with FRAX assessment tool and bone turnover markers (BTM) in women with diagnosed as postmenopausal osteoporosis for the first time. Materials and Methods: After exclusion of the causes of secondary osteoporosis 61 postmenopausal women diagnosed with osteoporosis for the first time were enrolled. Height and weight measurements, comorbid diseases, menopause age, and laboratory investigations were recorded. Lumbar and femur neck and femur total T scores were measured by dual-energy x-ray absorptiometry (DXA). As BTM, serum osteocalcin (OC) and urine deoxypridinoline levels were measured. 10-year fracture risk of hip and major osteoporotic fracture was calculated with FRAX assessment tool. Results: The mean age of patients was 61±39 years. Median value of menopause year was 15.13 years (min: 2, max: 40). The median 10-year hip fracture and major osteoporotic fracture risks were calculated as 1.10% (min: 0, max: 23), 6.9% (min: 3, max: 34) respectively. There was no significant relationship between BTM and fracture risk. Positive significant correlation was found between menopause year and hip fracture risk, and between menopause year and major osteoporotic fracture risks (p=0.031, 0.276; p=0.025, r=0.287). Negative significant correlation was detected between body mass index and hip fracture risk (p=0.002, r=-0.392). Conclusion: In our study, we couldn’t find relationship between BTM and fracture risks assessed by using FRAX tool in patients with initially diagnosed of postmenopausal osteoporosis. Further studies are needed to investigate the relationship between BTM and fracture risk in different patient groups. (Turkish Journal of Osteoporosis 2015;21: 58-62)